GENDER ANALYSIS OF MAIZE PRODUCTION AMONG SMALL SCALE FARMERS IN IFE EAST AND AYEDAADE LOCAL GOVERNMENT AREAS OF OSUN STATE - OGUNLEYE , A. S.; ADEYEMO , R.; BINUOMOTE, S. O.; OJO, T. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The paper examined the performance of maize farm households in Ayedaade and Ife East Local Government Areas in Osun State, Nigeria. The paper focused on socioeconomic differences; and costs and returns to production among small scale maize farmers within the gender mainframe. Using a set of pre-tested questionnaire, primary data was collected from 120 respondents in the study area. The analysis was undertaken using descriptive statistics, multiple regression and farm budgetary analyses. Results showed that the average age of 85.40% of male and 89.50% of female farmers ranged between 21-50 years, the male farmers (74.4%) were more educated than their female counterparts (47.4%) and 92.7% of the male farmers cultivated between 1-7 hectares of farm land as against 42.1 % of the female farmers in the same category. However, there were no significant differences (except in household size and farming experience) between the socio-economic characteristics of male and female maize farmers. Results also revealed that socioeconomic factors such as age and years of formal education; and quantity of factor inputs such as size of farm land and quantity of fertilizer used were major determinants of the value of maize output in the study area. Generally, maize farming was profitable in the area because the gross margin per Naira invested showed that every N1.00 invested per hectare yielded N2.82 and N5.38 for male and female farmers, respectively.